A Framework of Retailer-Manufacturer Cooperation and Coopetition: Consumer Durable Goods Retailersâ€™ Case Studies - Marzanna Katarzyna Witek-Hajduk; Anna Napiórkowska (Entrepreneurial Business and Economics Review)
Objective: The purpose of this paper is to develop a framework of cooperation and coopetition between retailers and key manufacturers from a perspective of retailers offering consumer durables.